2022
DOI: 10.1155/2022/1090034
|View full text |Cite
|
Sign up to set email alerts
|

Novel Application of Eupatilin for Effectively Attenuating Cisplatin-Induced Auditory Hair Cell Death via Mitochondrial Apoptosis Pathway

Abstract: Eupatilin (5,7-dihydroxy-3 ′ ,4 ′ ,6-trimethoxyflavone) is a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…19 It has antioxidant and anti-apoptotic effects against cisplatin-induced ototoxicity, as well as inhibiting inflammatory responses and aging in nucleus pulposus (NP) cells. 20,21 In addition, a derivative of Eupatilin to treat dry eye disease is being developed and is undergoing Phase I study. 22 Eupatilin can also reduce the inflammatory response in LPS-induced rats, decreasing the level of surfactant protein (SP)-A, SP-D, and inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%
“…19 It has antioxidant and anti-apoptotic effects against cisplatin-induced ototoxicity, as well as inhibiting inflammatory responses and aging in nucleus pulposus (NP) cells. 20,21 In addition, a derivative of Eupatilin to treat dry eye disease is being developed and is undergoing Phase I study. 22 Eupatilin can also reduce the inflammatory response in LPS-induced rats, decreasing the level of surfactant protein (SP)-A, SP-D, and inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%
“…S3A-K ). In these experiments, superoxide was monitored using CellROX Green (localizes primarily to the nucleus and mitochondria) and mitoSOX (localizes primarily to the mitochondria); H 2 O 2 levels were probed with Amplex Red (27,28). We observed that expression of Ec STH and mito Ec STH did not impact the total cellular GSH/GSSG ratio ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between cisplatin and oxidative stress has been well established ( Gentilin et al, 2019 ; Kros and Steyger, 2019 ; Sheth et al, 2017 ), and prior studies demonstrate that mitochondria play a key role in cisplatin-induced oxidative stress in cancer and non-cancer cell lines ( Marullo et al, 2013 ) as well as hair cells ( Li et al, 2021 ; Lu et al, 2022 ). Here, we build on this literature and demonstrate that oxidative stress occurs shortly after cisplatin exposure.…”
Section: Discussionmentioning
confidence: 99%